Junctional microstructure of the non-sticky spiral scaffold in the golden orb web spider, Trichonephila clavata - Seung-Min Lee; Myung-Jin Moon (Applied Microscopy)
Abstract The non-sticky spiral silk, which typically serves as a temporary structural component in most orb-weaving spiders, functions as a permanent scaffold in the golden orb-web spider (Trichonephila clavata). Composed of double strands approximately 4 μm in diameter, the non-sticky spiral forms robust extended junctions exceeding 200 μm in radius. The muscular cell layer observed within the pyriform gland facilitates the active extrusion of pyriform fibers and cement, enabling efficient wrapping at the junctions. These robust junctions stand in stark contrast to the loose, droplet-mediated adhesion seen in sticky spirals, allowing the non-sticky spiral to enhance web stability and effectively prevent damage expansion. Furthermore, the non-sticky spiral plays an important role in localized web repair by replicating the original web's loop patterns to restore damaged areas. These findings suggest that the non-sticky spiral stabilizes the wide intervals between radii in the lower hub region, providing enhanced resistance to external forces and repairing structural damages. The results also demonstrate the evolutionary significance of utilizing non-sticky spiral as a permanent component, facilitating the construction and maintenance of large, densely structured orb webs.